Evaluation of sociomoral values in students. Comparative research between Brazil and Spain - Avilés Martínez, José María; De Stefano Menin, Maria Suzana [UNESP]; Rossi Tavares, Marialva (My University, 2019)
Introduction: Educational policies on education in values and the improvement of school convivencia in countries such as Spain and Brazil have described different trajectories in their educational developments. How Spanish schools have been working for values education for decades, the Adherence to four moral values (Solidarity, Respect, Justice and Democratic Convivencia) among Spanish and Brazilian students (children and adolescents) with a scale validated in Brazil and adapted to the Spanish reality is compared here. These are Spanish students from Secondary Education Institutes and Brazilian students from Fundamental Teaching I and II. Method: It confronts the Spanish students (12-18 years old) and Brazilian students (10-18 years old) to moral dilemmas about the four values that are studied in which they have to position themselves choosing one of the options offered to them. The results place the students in four levels of adherence in each value (anti-moral value -I-, egocentric -II-, sociocentric -III and moral -IV-) from the Theory of Response to the Item (TRI). Results: The results show that Spanish students present a better development than the Brazilian one in terms of adherence to the four values measured in this research. The greatest differences are found in the values of Solidarity and Respect. It is the smallest student body who presents the most differences, but not the adolescent, especially in the Justice value, where their scores are similar. On the other hand, adherence to the Democratic Convivencia value seems insufficientin both samples. Discussion: The implementation of convivencia programs in the school is considered relevant to develop adherence to socio-moral values among students.
Evaluación de valores sociomorales en escolares. Estudio comparativo entre alumnado Español y Brasileño
Keywords: Convivencia; Education in sociomoral values; Evaluation; Justice; Respect; Solidarity